ANALISIS AKTIVITAS VALUE CHAIN TERHADAP KUALITAS PRODUK PADA UMKM BIKA AMBON - Ricky Widyanto; Dian Farindah Damanik; Farah Ananda Lubis; Titania Febrianti; Nurbaiti Nurbaiti (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
Micro,i Smalli andi Mediumi Enterprisesi (MSMEs)i arei onei ofi thei people'si businessesi thati havei ai significanti contributioni toi thei country'si economy.i Ani effectivei andi efficienti valuei chaini willi certainlyi makei businessi activitiesi ablei toi continuei toi survivei ini thei midsti ofi increasinglyi tighti industriali competition.i Ini accordancei withi thisi study,i thei influencei ofi valuei chaini activitiesi oni producti qualityi ini MSMEsi bikai amboni ini thei cityi ofi Medan.i Thisi studyi usesi ai descriptivei qualitativei methodi byi utilizingi secondaryi datai toi accessi thei latesti datai andi informationi relatedi toi thei Valuei Chaini oni producti qualityi ini MSMEsi bolui Bikai Amboni ini thei cityi ofi Medan.i Thei resultsi ofi thisi studyi arei thati thei applicationi ofi valuei chaini analysisi hasi ai significanti influencei oni improvingi thei qualityi ofi bolui Bikai Amboni products.i Byi conductingi detailedi mappingi ofi eachi stagei ini thei productioni processi -i startingi fromi thei procurementi ofi rawi materials,i thei productioni process,i toi distributioni -i MSMEsi bolui Bikai Amboni cani identifyi andi improvei importanti aspectsi thati affecti thei qualityi ofi theiri products. With the aim of identifying and evaluating each stage in the value chain that contributes to improving product quality, as well as providing strategic recommendations for MSME players to optimize their value chain management.